Membrane Permeability of Murine Oocytes and Embryos for 1,2-Propane Diol and Damaging Effect of its Concentrated Solutions - Pishko, O. V.; Smolyaninova, E. I.; Kovalenko, I. F.; Rozanov, L. F. (Problems of Cryobiology and Cryomedicine, 2004)
The permeability coefficients of plasma membranes of oocytes, 1-, 2- and 8-cell murine embryos for 1,2-propane diol (1,2-PD) and water molecules were determined. The fertilisation and embryo development stage were shown as not affecting the transport characteristics of cell membranes.